The Establishment of The Notary Office Law Article 37 Reviewed From The Political Perspective of National Law - Rahayu Putri Wulansari (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2023)
The political notion of notarial law is urgently needed in the its affairs aspect, especially after the amendment of the UUJN, bearing in mind that there are regulations that came after the amendment of the law. Changes to the UUJN itself are legal politics in the notary because there are several articles in the UUJN which are still concise, even though generally and clearly stated “explanatory attachments” such as Article 37 of UUJN National legal politics as a basic guideline for all forms and processes of formulation, formation, and development of law in the country. If the national legal politics is the basic guideline for all forms and processes of formulating, forming, and developing laws in the country, it can be ensured that national legal politics must be formulated in a statutory regulation that is also fundamental, not in a technical statutory regulation.